A Meta-Analysis of Sustanainability Development Goals (SDGs) During the Covid-19 Pandemic - Rifaid, Rifaid; Abdurrahman, Abdurrahman; Rahmi, Siti Atika; Kurniawan, Cahyadi (Jurnal Pemerintahan dan Politik Lokal, 2024)
This study is a bibliometric analysis to determine the map of the development of the sustainability study of development goals during the COVID-19 pandemic by searching through Scopus with the keywords "SDGs" "COVID-19" in various international journals. The authors used the Scopus search engine to find random journals and identify publications related to sustainable development goals. This study implemented a data visualization software called VOSviewer to find out biometric Bil maps to analyze the results and trends in information production in the Sustainability Development Goals during the COVID-19 pandemic. The theme was then integrated into the Nvivo 12 plus software to produce the Sustainability Development Goals project. This study indicated that the development of research in 2021 is immensely increasing. The development of the dominant theme processed in NVivo12 Plus showed that the most prevalent word development appeared. Sustainability Switzerland journals published the most articles and were seen from research articles, followed by reviews, conference papers, notes, and editorials. The relationship theme in the Sustainability Development Goals (SDGs) studies during the COVID-19 pandemic was divided into 7 clusters or seven parts.